Open-Label Allopregnanolone Treatment of Men with Fragile X-Associated Tremor/Ataxia Syndrome - Wang, J.Y.; Trivedi, A.M.; Carrillo, N.R.; Yang, J.; Schneider, A.; Giulivi, C.; Adams, P.; Tassone, F.; Kim, K.; Rivera, S.M.; Lubarr, N.; Wu, C.-Y.; et al. (Neurotherapeutics, 2017)
Fragile X-associated tremor/ataxia syndrome (FXTAS) is a late-onset neurodegenerative disorder affecting approximately 45% of male and 16% of female carriers of the FMR1 premutation over the age of 50 years. Currently, no effective treatment is available. We performed an open-label intervention study to assess whether allopregnanolone, a neurosteroid promoting regeneration and repair, can improve clinical symptoms, brain activity, and magnetic resonance imaging (MRI) measurements in patients with FXTAS. Six patients underwent weekly intravenous infusions of allopregnanolone (2–6 mg over 30 min) for 12 weeks. All patients completed baseline and follow-up studies, though MRI scans were not collected from 1 patient because of MRI contraindications. The MRI scans from previous visits, along with scans from 8 age-matched male controls, were also included to establish patients' baseline condition as a reference. Functional outcomes included quantitative measurements of tremor and ataxia and neuropsychological evaluations. Brain activity consisted of event-related potential N400 word repetition effect during a semantic memory processing task. Structural MRI outcomes comprised volumes of the hippocampus, amygdala, and fluid-attenuated inversion recovery hyperintensities, and microstructural integrity of the corpus callosum. The results of the study showed that allopregnanolone infusions were well tolerated in all subjects. Before treatment, the patients disclosed impairment in executive function, verbal fluency and learning, and progressive deterioration of all MRI measurements. After treatment, the patients demonstrated improvement in executive functioning, episodic memory and learning, and increased N400 repetition effect amplitude. Although MRI changes were not significant as a group, both improved and deteriorated MRI measurements occurred in individual patients in contrast to uniform deterioration before the treatment. Significant correlations between baseline MRI measurements and changes in neuropsychological test scores indicated the effects of allopregnanolone on improving executive function, learning, and memory for patients with relatively preserved hippocampus and corpus callosum, while reducing psychological symptoms for patients with small hippocampi and amygdalae. The findings show the promise of allopregnanolone in improving cognitive functioning in patients with FXTAS and in partially alleviating some aspects of neurodegeneration. Further studies are needed to verify the efficacy of allopregnanolone for treating FXTAS.